RELATIONSHIP OF THE INFLATION RATE AS A RISK FACTOR IN THIRD CATEGORY IR COLLECTION IN PERU 2020-2024 - Montoya Alva, María (2025)
This article uses statistical data from official sources including SUNAT and the BCRP to analyze the relationship between third-category income tax collection in Peru from 2020 to 2024 and the inflation rate as a risk factor. The study analyzed data using descriptive, correlational, and explanatory methods. According to the findings, there was a positive link between January 2020 and December 2024, as indicated by the Pearson correlation coefficient of 0.313. It is determined that the R² coefficient is 0.0979, which indicates that the tax collection from third category income only accounts for 9.8% of the inflation rate as a risk factor. Future research could focus on other risk areas and expand the study using more current data. Keywords: inflation, risk factors, income tax, CPI.